River Water Quality Classification in Special Region of Yogyakarta Using Multi-Layer Perceptron - Meily Vira Ellisthia; Agus Suhendar (Komunitas Dosen Indonesia, 2025)
River water quality in the Special Region of Yogyakarta has declined significantly in recent years due to rapid urbanization and increasing anthropogenic pressures, causing several physicochemical and biological parameters to exceed environmental quality thresholds. To address the need for a consistent, data-driven assessment framework, this study develops an optimized river water quality classification model using a Multi-Layer Perceptron (MLP) architecture enhanced by Grid Search Cross-Validation. A critical challenge in the dataset is the severe class imbalance, particularly the dominance of the